Salmon lice loads on Atlantic salmon smolts associated with reduced welfare and increased population mortalities - SC Ives; JD Armstrong; C Collins; M Moriarty; AG Murray (Aquaculture Environment Interactions, 2023)
Modelling potential impacts of salmon lice Lepeophtheirus salmonis on Atlantic salmon Salmo salar requires estimation of the levels that cause serious sub-lethal physiological impacts and direct mortality. Here we analysed results from existing laboratory experiments to identify 2 thresholds; the lower threshold (T1) estimates the level at which lice loads cause systemic sub-lethal effects on smolts likely to impact performance, and the upper threshold (T2) identifies the lice load causing direct mortality. T1 is an empirical value based on a catalogue of lice impacts according to impact type (superficial or systemic) and concentration, converted from a range of experiments. The onset of these indicators of welfare and behavioural impacts indicates T1 ≈ 0.08 lice g-1 of host. T2 represents 50% probability of onset of mortality under laboratory conditions quantified using a dose-response curve based on data collated from studies where mortality has occurred or not at specified lice concentrations. T2 ≈ 0.24 lice g-1 with a bootstrapped 95% confidence interval between 0.1 and 0.67 lice g-1. These thresholds offer both an amending of the current approach to the management of lice concentrations on fish in the form of a sub-lethal welfare threshold and further evidence to support mortality-based lice thresholds already in use.